Development Of Integrated Monitoring System For Re-Electric Vehicle - Kasrul, Abdul Karim; Md Nazri , Othman; Auzani , Jidin; Mohd Zulkifli, Ramli (Sains Humanika, 2014)
Awareness of technological development of an electric vehicle (EV) has increased from year to year, particularly with commercialization of the electric vehicles in the consumer market. In contrast to the internal combustion engine (ICE) vehicles based on gasoline, electric vehicles rely on the batteries as the sole energy source. Although the electric vehicles have a relatively simple structure and their operations are more environmentally friendly, the battery energy capacity is limited, high in price and requires long charging time which as a result will limit the driving distance. Therefore, to tackle these issues a dedicated monitoring system for the battery is designed and developed. The developed integrated monitoring system consists of graphical display,measuring circuitries, speedometer, GPS, gyro and the controller module that monitors the batteries' status as well as other parameters that are important for the safe operation of electric vehicles. In addition the data was recorded during the driving for research purpose and future references, and the safety aspects are embedded in the controller module. The development of the system and its algorithm is described in this paper. The integrated monitoring system was tested in a real driving conditions to verify the functionality. The results show that the system is capable to measure and record all key parameter values, especially related to individual batteries along the journey. It also provides the user with a high degree of reliability through interactive and informative graphical display. As a conclusion, the use of the integrated monitoring system is not only able to ensure the efficient use of the battery and prolong its life span but also the safety aspect is considered in the design. For further system improvement, the battery characteristic,regenerative braking and traffic conditionswas incorporated into the algorithm.